Farm production in England, 1700-1914 - Turner, Michael Edward (Oxford University Press, 2001)
A study of English agriculture in the 18th and 19th centuries based on the records of the farmer, this book shows that the agricultural revolution can be located in the first half of the 19th century as farmers fed a growing urban population.